STUDIES OF TOXIGENIC AND ZOOPATHOGENIC FUNGI ASSOCIATED WITH THE SPOILAGE OF NIGERIAN POULTRY FEEDS (1988)
Six species of known toxigenic and zoopathogenic fungi were isolated from Nigerian poultry feeds. These include Aspergillus flavus Link: Fr. (IMI 280819), A. fumigatus Fres. (1M1 280822), A. niger v. Tieghem (IM1 280823), A. oryzae (Ahlburg) Cohn (IM1 280831), Rhizopus arrhizus Fischer (1M1 280827) and Rhizomucorpusillus Lindt Schipper (1MI 280824). Growth-temperature range for the fungi was between 15° and 45°C. Aspergillus fumigatus and Rhizomucor pusillus are thermotolerant with optimum growth 40° C while Rhizopus arrhizus had optimum growth at 30° C. For Aspergillus flavus, A. niger and A. oryzae the optimum growth was at 35° C. The pH growth studies showed that all the fungi had good mycelial growth at pH 4-8 with optimal growth at pH 5.5 for Aspergillus fumigatus, A. flavus and A. oryzae. Aspergillus niger, Rhizomtlcor pusillus and Rhizopus arrhizus had optimal growth at pH 6.0. Nutritional studies showed that all the fungi were capable of utilizing the various forms of carbon and nitrogen provided to varying extents. Starch and dextrin were excellent sources of carbon for mycelia growth and sporulation while pectin and carboxymethyl cellulose (CMC) were poorly utilized by all the fungal isolates. The fungal species grew poorly on native cellulose (filter papers) except Rhizomucor and Rhizopus arrhizus which showed no growth pusillus on this carbon source. Apart from tryptophan, all the nitrogen sources supplied were utilized for growth and sporulation by the test fungi though to the best nitrogen source varying extents. Casein was for all the fungi. Feed infusion medium also supported growth and sporulation of all the isolates. Varying quantities of aflatoxins (B(1), B(2_ and G(2)) were produced by Aspergillus flavus and A. oryzae on modified Czapek-Dox media. None of the remaining fungal species produced afaltoxin. Peak aflatoxin B(1) production was on the 8th day of incubation by the two toxigenic fungi. Optimum pH and temperature for the production of toxins were pH 5 and 300 C respectively. Major sources of aflatoxins in poultry feeds due to mould infestation in increasing order of importance were: palm kernel, corn and groundnut cake meals. Studies on aflatoxin production on feed concentrates by A. flavus and A. oryzae showed that under suitable conditions of moisture and temperature, dried brewers grains, wheat offals, palm kernel, corn and groundnut cake meals were suitable substrates for toxin production. Other feed concentrates: fish, blood, oyster shell and bone meals were found to be unsuitable substrates for aflatoxin production. Aflatoxins were not detected in poultry droppings before and after inoculation with the toxin producing fungi. All the fungal isolates produced extracellular amylases, cellulases, proteases and lipases. The synthesis and activity of these enzymes were affected by external factors such as the pH, incubation temperature and type of carbon source in the growth medium. Optimum activity for all the enzymes produced by the isolates was in acidic media (pH 4-6) and within a temperature range of between 40°C and 50°C. On the basis of these findings recommendations were made for the control of the toxigenic and zoopathogenic fungi in poultry feeds and other stored agricultural products.